Muslim women’s tourist gaze: a comprehensive systematic review - Asbollah, Asra Zaliza; Zakariya, Khalilah; Mansor, Mazlina (UiTM Press, 2024)
This literature review examines the overlooked experiences of Muslim tourists in particular women within tourism studies, focusing on their perspectives through the "tourist gaze." It explores the cultural, religious, and gendered encounters of Muslim women in tourism, addressing the challenges and opportunities influenced by their beliefs and contexts. Despite their increasing presence, there's a lack of comprehensive understanding of how Muslim women perceive tourist spaces. Employing a systematic approach, the review synthesizes existing literature, using keywords to identify relevant studies and applying stringent criteria for selection. Through rigorous analysis, key themes emerge, including religious observance, cultural identity, gender roles, empowerment, and challenges. The review sheds light on how Muslim women's gaze is shaped by faith, cultural practices, and societal expectations, influencing their interactions with tourist destinations and other tourists.